Purification and characterization of thermostable alpha‐amylase from Geobacillus sp. DS3 from Sikidang Crater, Central Java, Indonesia - Dea Rizki Widiana; Sotharith Phon; Andriati Ningrum; Lucia Dhiantika Witasari (Universitas Gadjah Mada, 2022)
Amylases are considered the most essential enzymes in biotechnology since they are widely utilized in the textile, food processing, and detergent industries. It is necessary to explore extracellular enzymatic activity in several microorganisms to discover a new potential application from amylases. In a previous study, thermophilic bacteria Geobacillus sp. DS3 isolated from Sikidang Crater, Dieng Plateau, Central Java, Indonesia showed amylase activity in starch medium at 70 °C. This study aimed to purify and characterize the thermostable alpha‐amylase from Geobacillus sp. DS3. The alpha‐amylase was produced and purified using ammonium sulfate and DEAE Sephadex A‐25 column. The enzyme activity was determined using the 3,5‐dinitrosalicylic acid (DNS) method. Geobacillus sp. DS3 optimally produced the alpha‐amylase at 60 °C for 15 h. The alpha‐amylase exhibited high enzymatic activity in 40–60% saturated ammonium sulfate extract. The molecular weight of the enzyme was estimated to be 58 kDa. The thermostable alpha‐amylase showed activity at the optimum temperature of 50 °C in 200 mM sodium phosphate buffer pH 7.0. The enzyme was inhibited by EDTA, PMSF, 2‐ME, and mostly by HgCl2. The Km and Vmax of the pure enzyme were 235.43 mM and 1428.57 U/mL, respectively. The result suggested that the purified thermostable alpha‐amylase from Geobacillus sp. DS3 offers potential application in areas of the food industry, such as the bakery industry.